PEMILIHAN ENGINEERING CONTRACTOR PROYEK DANA HIBAH ENERGI TERBARUKAN DENGAN METODE DEMATEL DAN ANP - Pambudi, Agus Setyo (BISMA: Jurnal Bisnis dan Manajemen, 2018)
One of the success keys of the grant fund program for the renewable energy project is in the decision making process to find the engineering contractor with the best quality, effectiveness, and efficiency to implement the process of procurement of goods and services. The objective of this research is to design a systematic selection model for the engineering contractor referring to the conditions, situations, and scopes as required by the "Y" institution. Data were processed using Decision Making Trial and Evaluation Laboratory (DEMATEL) and Analityc Network Process (ANP). The decision criteria referred to the PEPRES No. 70/2012, PERMEN No. 08/PRT/M/2011, and the results of Focus Group Discussion (FGD) conducted by the evaluation team. The assesments from the evaluation team were including internal and financial capability, technical capability, organizational capability, commitment to quality assurance, commitment to health and safety, and pricing. Keywords: Selection of Engineering Contractor, Grant Fund, Renewable Energy, Decision Making Trial and Evaluation, Analytic Network Process.